Determination of Monetary Transmission through the Types of Credit on Economic Growth - Sipahutar, Mangasa Augustinus (Universitas Negeri Malang, 2018)
Banks credit by usage (working capital, investment and consumer credit) and by economic sectors (agricultural, mining, industrial, trade and services) on Indonesian economic growth explainedthe role of banks credit as a monetary transmission channel. Banks credit for investment, agricultural, industrial, trade and services, have a significant effect on economic growth. Thus, as a growth accelerating factor, investment credit aimed to financing agricultural, industrial, trade and services areable to promote qualified growth of Indonesian economy as well as reducing unemployment rate. This study uses bankscredit data by usage, economic sectors, economic growth and unemployment rate in the period of 1991-2014. Model estimation on the relationship between banks credit by usage on economic growth and unemployment using ECM (Error Correction Mechanism) model, while the relationship between banks credit by economic sectors oneconomic growth using in?difference regressionon OLS (Ordinary Least Square) model.Credit depth as the ratio between banks credit and economic growth is only appropriate for the analysis of banks credit relationship usage on economic growth, while by economic sectors, their role depend on the magnitude of credit portfolio to total banks credit.Keywords: credit by economic sectors; credit by usage; economic growthJEL Codes: E6, O2, O4